2016
DOI: 10.1007/s00009-016-0787-4
|View full text |Cite
|
Sign up to set email alerts
|

Exponential B-Splines for Numerical Solutions to Some Boussinesq Systems for Water Waves

Abstract: In the study, the collocation method based on exponential cubic B-spline functions is proposed to solve one dimensional Boussinesq systems numerically. Two initial boundary value problems for Regularized and Classical Boussinesq systems modeling motion of traveling waves are considered. The accuracy of the method is validated by measuring the error between the numerical and analytical solutions. The numerical solutions obtained by various values of free parameter p are compared with some solutions in literatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Use Kink type wave solution of the Gardner equation is [17] We choose homogeneous Neumann conditions. We compute the numerical solutions using the selected values α=1, β=-5 and µ=1 with different values of time step size Δt.…”
Section: Kink Type Wave Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Use Kink type wave solution of the Gardner equation is [17] We choose homogeneous Neumann conditions. We compute the numerical solutions using the selected values α=1, β=-5 and µ=1 with different values of time step size Δt.…”
Section: Kink Type Wave Propagationmentioning
confidence: 99%
“…Recently trigonometric B-splines have been adapted to construct numerical techniques for getting solutions of differential equations such as diffusion problems, Fisher equation and Burger equations in [12,13,14]. Quintic trigonometric Bspline functions are newly defined basis function that are different from polynomial [15,16], exponential [17,18] ones but in the family of trigonometric B-splines. Also trigonometric quintic B-spline collocation method was applied to solve coupled Burgers' equation system in [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in [2] it is shown that exponential splines play an important role in setting up a one-to-one correspondence between dual pairs of Gabor frames and dual pairs of wavelet frames. For an application to some numerical methods, we refer the interested reader to [5] and [12]. In [15], a new class of more general cardinal exponential B-splines, so-called cardinal exponential B-splines of complex order, was introduced, some properties derived and connections to fractional differential operators and sampling theory exhibited.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they applied collocation of cubic B‐splines finite element method to solve symmetric regularized long wave equations . Furthermore, there are lots of paper about collocation method to solve partial differential equations using B‐splines . In this paper, we use the collocation method and interpolation method via cubic B‐spline functions and bicubic B‐spline functions to solve one dimensional and two dimensional nonlinear stochastic quadratic integral equations, respectively.…”
Section: Introductionmentioning
confidence: 99%